Analisis Pembagian Harta Warisan Kepada Ahli Waris Menurut Hukum Perdata (BW) - Dika Ratu Maru’atun; Dwi Juniyanto; Wahyu Rivaldi; Asep Sunarya (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Current developments have brought many changes to Indonesia. The many changes that have occurred have not changed one thing in Indonesia, namely heritage. This problem is what triggers arguments between families and the Indonesian people because they don't want to know how inheritance is distributed according to civil law, so as a result they divide inheritance assets at will and do not comply with the Civil Code regarding inheritance. Article 830 of the Civil Code states that inheritance law is the law that regulates the legal position of a person's assets after he dies, especially the transfer of assets to other people. This research also aims to determine the distribution of inheritance assets to heirs according to civil law (BW). In BW (civil) inheritance law, in terms of inheritance, there are three important elements, namely Heir (erflater), Heir (erfgenaam) and Inheritance (Nalatenshap). In the Civil Code there are four groups of heirs, namely Group I, Group II, Group III and Group IV. The research method used is a normative legal research method, namely legal research which focuses on literature study and the data used in this research is in the form of books, journals, laws, other references which are collected and processed to be presented to meet the need for new knowledge and ideas.